Kulturarv som resurs i socialt hållbar stadsutveckling : En gestaltad livsmiljö för framtiden - Söderström, Ulrika (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2024)
Claiming that cultural heritage must be preserved for sustainable urban development and for the benefit of future generations is common practice in cultural heritage management and urban planning. But when cultural heritage is used as a resource in urban transformation processes, do current heritage practices, including archaeology, promote the socially sustainable urban futures they aim to achieve? This research aims to generate new knowledge on how Swedish contract archaeology can contribute to sustainable urban development and goodliving environments in an informed and innovative manner. By adopting a broad perspective, I explore how cultural heritage is utilized as a resource in urban transformation and design processes to promote social sustainability. Employing an interdisciplinary theoretical framework, I examine how the social sustainability effects of current heritage practices, including archaeology, affect sustainable futures making. The research includes three case studies on urban transformation: the Caroli quarter in Malmö (1967–1973), the Valnötsträdet quarter in Kalmar (2008–2018), and the ongoing transformation of Kiruna town. The results highlight how contradictions between legislation's focus on the past and cultural and urban planning's future-oriented goals institutionalize ideas about cultural heritage value and the perception that preservation is a sustainable heritage practice in itself. Consequently, archaeology is rarely seen as a process or practice that promotes social sustainability. Instead, focus is on the value of the built historic environment and stories about the past, assuming that using these elements in development and design processes will promote present and future sustainability values, such as attractiveness, security, social cohesion, and collective identities. However, the results show that expected social sustainability goals are rarely met due to a lack of citizen participation and a lack of understanding of what is required to achieve these goals in the present and ...